Little-known Asian animals with a promising economic future : report of an ad hoc panel of the Advisory Committee on Technology Innovation, Board on Science and Technology for International Development, Office of International Affairs, National Research Council. (National Academy Press, 1983)
Materia preliminar – Introducción -- Especies bovinas domesticadas -- Especies bovinas salvajes --Cerdos y especies parecidas -- Recomendaciones y necesidades generales de investigación – Apéndices -- Apéndice A: Lecturas seleccionadas -- Apéndice B: Contactos de investigación -- Comité Asesor sobre Innovación Tecnológica -- Junta de Ciencia y Tecnología para el Desarrollo Internacional (BOSTID) -- Publicaciones de BOSTID.